Probabilistic assessment of design error costs - Love, Peter; Lopez, R.; Kim, J.; Kim, M. (American Society of Civil Engineers (ASCE), 2014)
The statistical characteristics of design error rectification costs experienced in 139 Australian construction projects are analyzed. Theoretical probability distributions are fitted to the design error cost data. A generalized Pareto probability function was found to provide the best overall distribution fit for design error costs. The generalized Pareto distribution is used to calculate the probability of design error costs being experienced for the selected sample. A mean design error cost of 14.2% of a project's contract value is reported. A significant difference between mean design error costs and project types was found for civil engineering (23.44%) and fit-out (22.50%) projects. Projects >Australian dollars (A$)101M were found to experience significantly higher mean design error costs (26.18%) than other projects. Being able to determine the likelihood of design error rectification costs from the derived empirical probability distribution will provide an ameliorated assessment of risk before the commencement of construction. Strategies to reduce design error rectification costs are also discussed. © 2014 American Society of Civil Engineers.